Analysis of the association between long-term exposure to low-dose ionizing radiation and dyslipidemia and its components in medical radiologists: The mediating role of inflammatory markers - Changyong Wen; Xiaolian Liu; Yiqing Lian; Weizhen Guo; Lingyu Zhang; Yanting Chen; Xin Lan; Mingfang Li; Sufen Zhang; Weixu Huang; Jianming Zou; Huifeng Chen (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Introduction: Our study aimed to explore the association between long-term exposure to low-dose ionizing radiation (LDIR) and dyslipidemia and its components among medical radiologists, and to identify the mediating role of inflammatory markers. Methods: This cross-sectional study was conducted on 3918 medical radiologists, with data collected through questionnaires and occupational external exposure dosimeters. The multifactorial logistic regression and restricted cubic spline model were used to analyze the association between long-term exposure to LDIR and dyslipidemia and its components among medical radiologists, and mediation analysis was used to identify potential mediation effects. Results: Of 3918 medical radiologists, 995 (25.4 %) had dyslipidemia. The gender, age, body mass index (BMI), and smoking status were influential factors for dyslipidemia of medical radiologists. After adjusting for confounders, the OR and 95 % CI for the occurrence of dyslipidemia and high TG in the highest tertile group (Q3) were 1.32 (95 % CI: 1.04, 1.67) and 1.51 (95 % CI: 1.11, 2.07), respectively. Restricted cubic spline model showed that the cumulative effective dose was linearly associated with both dyslipidemia and high TG, and the risk of dyslipidemia and high TG increased with the cumulative effective dose. Mediation analysis suggested that the inflammatory marker SII significantly mediated the association between cumulative effective dose and TG levels. Conclusion: Our study shows that medical radiologists have a high detection rate of dyslipidemia, and the risk of dyslipidemia and high TG increases with increasing cumulative effective dose. Inflammatory marker SII may play a mediating role in the association between cumulative effective dose and TG levels.